Math, asked by yashaswidubey1237, 3 months ago

Question 2. Write the following statement in the form of an equation: If you subtract 3 from 6 times a number, you get 9 (a) 3x – 6 = 9 (b) 6x – 3 = 9 (c) 6x + 3 = 9 (d) 3x + 6 = 9

Answers

Answered by shch4747
0

Answer:

(b) 6x - 3 = 9

Step-by-step explanation:

Let the number be x,

ATQ,

we are subtracting 3 from 6 times x and getting 9

this means we are subtracting 3 from 6x and getting 9

this means we are getting 9 by 6x-3

this means that 6x-3=9

So, (b) 6x - 3 = 9

Answered by Soundaryasarvade
0

Answer:

6x-3=9

Step-by-step explanation:

Subtract 3 -----   -3

from 6 times a number ------- 6*x = 6x-3

result will be 9

so, 6x-3=9

Similar questions